Faktor Atribut Produk pada Pengguna Ponsel Merek Nokia - Meidya Rahmawati; Wheny Khristianto (Jurnal Ilmiah ESAI, 2010)
Product attribute is one of important factor which influences purchasing of a product especially cellullar phone. Nokia as a market leader of cell phone in Indonesia realizes that product attribute is very important in maintaining its superiority. The type of this research is verified descriptive. The population of this research is Study to Regular S1 Degree Students of 2005-2007 of FISIP of Lampung University who use Nokia. Sample is decided by using slovin formula for 86 students. Random sampling technique with questionnaire and likert scale is used. Data analysis in the research is factor analysis. According to analized factor test, it is revealed that there are 12 indicators forming 3 factors. Those factors are; 1) product feature ; 2) product design and 3) product quality.Â Key Words : Factor Analysis, Product Attribute, Handphone